The Influence of Product Quality and Customer Satisfaction on Customer Loyalty - Sarwo Eddy Wibowo; Femmy Effendy; Sattar; Arni Kurniati; Dipa Teruna Awaludin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This research aims to examine and test the effect of product quality and customer satisfaction on customer loyalty at the Binama Tlogosari Semarang Sharia Cooperative. A quantitative approach was applied using multiple regression analysis to measure the relationship between variables. The sampling technique used accidental sampling, involving 73 respondents selected from cooperative customers. Data were collected through structured questionnaires and processed using IBM SPSS version 26 to ensure accurate and reliable results. The findings show that product quality has a positive and significant effect on customer loyalty. Customer satisfaction also demonstrates a positive and significant influence on loyalty. High product quality tends to build customer trust, while satisfaction encourages repeat transactions and long-term commitment. Both factors play an important role in maintaining stable relationships between customers and the cooperative. From a managerial perspective, maintaining consistent product standards and improving service quality are essential steps to sustain customer loyalty. Regular evaluation of customer perceptions and expectations is also necessary to support continuous improvement. Strong performance in these areas is expected to strengthen competitiveness and support the sustainability of the cooperative.